Accountability and transparency of accredited social enterprises in Malaysia: website disclosure analysis / Farah Aida Ahmad Nadzri ...[et al.] - Ahmad Nadzri, Farah Aida; Lokman, Norziana; Syed Yusuf, Sharifah Norzehan; Naharuddin, Saifuddin (UiTM Press, 2021)
Converging the three (3) traditional sectors: non-profits, for-profits, and government, a social enterprise (SE) is a hybrid business model that is primarily motivated by social or environmental objectives through entrepreneurship. SEs have gained wide attention from various stakeholders including beneficiary groups, customers, donors, partners, support groups, and government agencies. Therefore, to meet the demand of these various stakeholder groups, the SE needs to be accountable and transparent. Aiming to look at the website disclosure of the accredited SEs, this study analysed the content of the SEs websites based on the six (6) different dimensions. It was found that the overall disclosure was low at 31%. Based on the interview conducted, it was revealed that the low disclosure score was mainly due to a limited budget, time constraint, and lack of awareness among the SEs. It was also discovered that the majority of SEs focused more on disclosing their mission, vision, and values; besides information regarding the social or environmental activities conducted. Nevertheless, the information least disclosed by the accredited SEs were future outlook and strategies, and resource allocation, thus further improvement is suggested.